Psychology of insanity - "Hart, Bernard" (Cambridge, 1957)
This book lays no claim to be a comprehensive treatise upon the psychology of insanity. The number if independent schools of thought existing a the present day, and the fundamental divergence in their methods of investigation, make it obviously impossible to compress such a treatise into the limits of a small volume. All that has been attempted here is the presentation of certain recent developments in abnormal psychology which have already yielded results of fundamental importance, and which seem to offer an exceptionally promising field for further investigation.
Keywords: Psychology